HALAL COSMETICS IN THE EYES OF MILLENNIAL MUSLIMS: FACTOR ANALYSIS OF HALAL LABELS AND CELEBRITY ENDORSERS - Juliana Juliana; Aliya Nabila Azzahra; Rida Rosida; A. Jajang W. Mahri; Indra Fajar Alamsyah; Udin Saripudin (Universitas Airlangga, 2022)
This research aims to show the effect of the value of the halal label and celebrity endorser on purchasing decisions for halal cosmetic products with religiosity as a moderating variable. The method uses descriptive quantitative by analyzing the responses to questionnaires distributed to 228 respondents in Indonesia. Based on previous research, four hypotheses were built, and the collected data were processed using a path analysis tool through the Smart PLS 3.3.3 application. The results showed that the halal label variable and celebrity endorser significantly affected purchasing decisions for halal cosmetic products, with religiosity as a moderating variable. Meanwhile, the religiosity variable does not moderate the effect of the halal label and celebrity endorser on the decision to purchase halal cosmetic products. This finding confirms that religiosity has not sufficiently strengthened the influence of the halal label and celebrity endorser on the decision to purchase halal cosmetic products. In order to increase knowledge of Muslim halal in purchasing decisions for halal cosmetic products, the role of halal guarantee institutions and cosmetic manufacturers is needed in optimizing halal certification both from the content and production process. Business actors must increase awareness of the halalness of a product that can convince and encourage Muslim consumers, especially the millennial generation, to make decisions to purchase halal cosmetic products in Indonesia. This study is the first to examine the halal label and celebrity endorser on the decision to purchase halal cosmetic products with religiosity as a moderating variable and reveal its strength and weakness.